Radiation Effects on Thermal Decomposition of Neutron Activated Ammonium Perchlorate - Lokhande, R.S. (Asian Journal of Chemistry, 2010)
Isothermal decomposition of neutron activated ammonium perchlorate mixed with 3% by weight of NH4MnO4 was studied after giving 12 Mrad γ-radiation dose and heat treatment at 250 and 275ºC. The rate and the extent of decomposition increased at both the temperatures. The rate constants for accleratory and decay stages are calculated.